A oferta de ensino através dos anúncios de jornais sergipanos : a educação doméstica na casa do mestre e da família (1880-1930) - Lima, Maria José Torres (2018)
The present dissertation is in the field of Education History and has the purpose of analyzing the offer of education announced by teachers in the state newspapers, whose place of education was their own home or that of the student's family, during the 1853 to 1930. For that, a documentary and bibliographical analysis was carried out, including the investigation of the official documents (national and sergipana) and journalistic available in the collections of the State Council of Education - CEE / SE, of the Historical and Geographical Institute of Sergipe - IHGSE, and the Public Archive of the State of Sergipe, according to the delimited period. In order to base the historical analysis, we considered the socio-political context that conformed the Sergipe and Brazilian societies, at a time when the social, political, economic and educational changes were experienced due to the transition from the Imperial to the Republican system. In this sense, the efforts of the present study is to understand the processes of modernization through the history of existing and previous domestic education to the school system with the creation of school groups that, according to the historical studies of education, has settled unevenly in different regions of the Brazilian state. Our hypothesis is that fragility and the tests of installation of the state public educational order presented in Sergipe maintained and gave survival to the modality of education carried out in the private space of the house that, notwithstanding their profound transformations, persist in the current educational reality, under the guise of "banking teaching".